The bright boys : a history of Townsend Harris High School - Lebow, Eileen F. (Contributions to the study of education, 2000)
Annotation Townsend Harris High School in Manhattan was no ordinary high school. Named for the man who brought free higher education to New York City, students like Ira Gershwin, Yip Harburg, Adam Clayton Powell, Jr., Herman Wouk, Jonas Salk, and three future Nobel Laureates commuted from all five boroughs of the city in order to attend.